Green Marketing Analysis of Fore Coffee Purchasing Decisions With Green Products as Mediating Variables (Survey on Fore Coffee Consumers In The City of Sukabumi) - Aufa Salwa Hidayat; Dicky Jhoansyah; Kokom Komariah (LP2M IAIN Palopo, 2025)
This study aims to analyze the impact of Green Marketing on Fore Coffee Purchase Decisions, with Green Product as a mediating variable. In the context of increasing consumer awareness of environmental issues, a marketing strategy that focuses on sustainability is becoming increasingly important. The method used was a survey with a questionnaire distributed to 135 respondents of Fore Coffee consumers in Sukabumi City. The data obtained was analyzed using path analysis to test the relationship between the variables studied. The results of the study show that Green Marketing has a positive and significant influence on Green Products, and Green Products also have a positive effect on Purchase Decisions. In addition, Green Product serves as a mediating variable that strengthens the relationship between Green Marketing and Purchase Decisions. These findings suggest that an effective Green Marketing strategy can improve Green Products and in turn, influence consumer Purchasing Decisions. This research provides insights for companies in designing marketing strategies that are more sustainable and responsive to the needs of consumers who care about the environment.